Regulators, Conformers and Cowboys: The Enterprise Discourse, Power and Resistance in the UK Passive Fire Protection Industry. Issue 12 (December 2015) - Russell, Stephanie; McCabe, Darren
This article draws on industry-level research to explore the enterprise discourse in the UK passive fire protection industry. It highlights the theoretical weaknesses of the enterprise discourse by questioning the assumption that employers and managers necessarily support enterprise. It examines how employers, not just employees, may seek to resist or evade enterprise and how, far from offering a united front, employers may oppose each other. The article points towards the need for industry-level studies due to the limitations and potentially misleading insights that can flow from organization-level studies. Overall, it is argued that there may be more common ground between employees and employers in terms of opposition to enterprise than has previously been suggested.